Histórias de vida de formadores de professores de Ciências : paradigmas e princípios científico pedagógicos de formação docente - Silva, Paulo Sérgio Araújo da (2015)
It is a qualitative research in the narrative modality, whose research object implies life stories of former teachers of science teachers. I seek to investigate whether the knowledge of the life stories of former teachers of science teachers contribute to elucidate mechanisms of training choices of scientific-pedagogical aspects training liable to questioning in training course for teachers of scientific areas. In addition to investigating, how the knowledge of the life stories of former teachers of science teachers elucidates the way of each one to be inserted in or taking clearly 'paradigms' and 'principles' scientific-pedagogical teacher training? So I can understand in which conceptions of Education, Science, teaching, research and extension, the research subjects (un) believe over their lives and on what terms these conceptions are present in the way of each one constitute as a teacher trainer of teachers. Beyond that, I still seek to know the historic crossings with socio-political and cultural contexts that are present in the reported life stories. I try to identify to understand these relationships, from the study of memories, reports of life stories, evidence of which seem relevant in the constitution of the teaching professional in higher education in science just to understand what contributes to the constitution of the former of science teachers. In terms of methodology, this research uses life histories and autobiographies produced orally and taken into audio recording of subject teachers-trainers-of-teachers in science teaching area. These subjects were selected under the following criterion: professional formers who act in the training of biology, Physics, Chemistry and Science teachers or teacher training for early grades with respect to matters related to science education. Such trainers teachers - at number five subjects - have minimum experience of eight years of teaching in higher education. The life stories reported by them, point for discussions axis in the following areas: academic and non-academic reminiscences of former teachers of science teachers in their walk for professional choice and the emergence of formative aspects of teacher training and its relations / implications; the demarcation of socio-political and cultural contexts conditioning of teaching trainers teachers of teachers present in the reported life stories; explanation of constant knowledge of trainers of teachers life histories of science teachers from their inclusion in teacher training courses and thus elucidating the emergence of formative aspects. Generally various aspects or formative principles are listed through evocations, thus, master the scientific content, manifest / express views of scientific-pedagogical process, know how to plan, develop and evaluate educational activities (including ICT- information and communication technology), concieve the daily teaching practice as a research object, see how the ways of being and being in the profession (identity) are being handled by various social actors, emerge from the memories of trainers at intersections with other types of memories, namely, childhood and family reminiscences for life; the school where they studied; of higher education institutions that they have formed; academic meetings and conferences they attended by ... All that can, in the view of each one, have contributed in their way of being a former teachers of science teachers, elucidating their social roots. So formers teachers of teachers when reporting their life stories, show subjects in educational processes that insert into and/or take paradigms and scientific-pedagogical principles of teacher training, influences of traditional pedagogy (in which knowledge is reproduced, transmitted, unchanging, teaching is mechanical, decontextualized, characterized by the teacher verbalization, and the student is passive, uncritical), the emerging paradigm, and positivism, are recurrent.